Complex sleep apnoea in congestive heart failure. Issue 5 (10th March 2011) - Bitter, Thomas; Westerheide, Nina; Hossain, Mohammed Sajid; Lehmann, Roman; Prinz, Christian; Kleemeyer, Astrid; Horstkotte, Dieter; Oldenburg, Olaf
Abstract : Background: Sleep disordered breathing is common and of prognostic significance in patients with congestive heart failure (CHF). Complex sleep apnoea (complexSA) is defined as the emergence of central sleep apnoea during continuous positive airway pressure (CPAP) treatment in patients with obstructive sleep apnoea (OSA). This study aims to determine the prevalence and predictors for complexSA in patients with CHF with OSA, and to assess the effects of treatment with adaptive servoventilation. Methods: 192 patients with CHF (left ventricular ejection fraction (LVEF) ≤45%, New York Heart Association (NYHA) class ≥2) and OSA (apnoea–hypopnoea index (AHI) ≥15) were investigated using echocardiography, cardiopulmonary exercise testing, measurement of hyperoxic, hypercapnic ventilatory response, 6 min walk test and measurement of N-terminal pro-brain natriuretic peptide (NT-proBNP) prior to CPAP introduction. If patients demonstrated complexSA (AHI >15/h with <10% obstructive events) during CPAP titration, adaptive servoventilation was introduced and the investigations were repeated at 3 monthly follow-up visits. Results: ComplexSA developed in 34 patients (18%) during CPAP titration. After adjustment for demographic and cardiac parameters, measures of CO2 sensitivity (higher hyperoxic, hypercapnic ventilatory response) were independently associated with complexSA. Patients using adaptive servoventilation had improved AHI, NYHA class, NT-proBNP concentration, LVEF, hyperoxic, hypercapnic ventilatory response, oxygen uptake during cardiopulmonary exercise testing and the relationship between minute ventilation and the rate of CO2 elimination (VE/Vco 2 slope) at last individual follow-up (14±4 months). Conclusion: There is a high prevalence of complexSA in patients with OSA and CHF, and those who develop complexSA have evidence of higher respiratory controller gain before application of CPAP. Treatment with adaptive servoventilation effectively suppressed complexSA and had positive effects on cardiac function and respiratory stability.